The Problems of Enrollment-Retention-Graduation Rates in Higher Education in the United States - Owoye, Oluwole; Pan, Zuohong; Lumbantobing, Rotua (American Journal of Education and Practice, 2025)
Purpose: This study highlights the problems of low enrollment-retention-graduation rates (ERGR) in colleges and universities in the United States. Low ERGR poses significant challenges, thus many public colleges and universities face potential closure and/or merger; therefore, they need strategic improvements in order to maintain their academic viability. Materials and Methods: This study addresses two critical factors that can explain why public colleges and universities not Ivy Leagues, Public Ivies, and highly selective elite colleges and universities are struggling with ERGR. We use hedonic price and revealed preference theories to highlight the hedonic university education mindset (HUEM) of high school students in the United States. Using the hedonic price theory, we constructed the HUEM curve of high school students to reveal their preferences of colleges and universities. Given the declining population growth rate, we measured the fertility rate gap (FRG) to provide the statistical analyses to show the impact on low ERGR in higher education. Notably, HUEM and FRG are two critical factors used to provide a comparative analysis of the national trends in ERGR over the 1980-2024 period. In addition, we highlight the trends in ERGR and FRG by using the difference-in-means technique to test the average difference over the 1980-1999 and 2000-2024 periods. Finally, we estimated a parsimonious regression to show the impact of FRG on ERGR. Findings: The estimated regression results showed that FRG has statistically significant negative effect on ERGR. Interpretatively, a negative FRG will result in fewer students in elementary, middle, and high schools, thus leading to lower ERGR in public colleges and universities. Unique Contributions to Theory, Practice and Policy: It is recommended that enrollment officers need to let high school students know that their colleges and universities provide high quality education similar to the Ivy League, Public Ivies, and other highly selective elite academic institutions.